Court Street Bridge and Lehigh Valley Railway Station, Rochester, N.Y. - (:unkn) unknown (Printed by Technor Bros. Inc., at Cambridge Mass., USA, 2009)
A Stone arch bridge over the Genesee River on Court Street was built in 1893, leading to the Lehigh Valley railway Station which was chartered in 1846 to bring coal for the coal fields of Pennsylvania.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Postcards; United States; Cities and towns--United States--Rochester; Bridges--United States; Railroad stations--United States; Rivers--United States